The Teaching Reform and Practice of Ideological and Political Construction on the Principles and Applications of Database Course in the Digital Intelligence Era - Zhao, Youen (Journal of Educational Research and Policies, 2025)
As the new orientation, new requirement and new task to develop higher education, it is necessary to deeply implement the digital strategic action, construct a new form of higher education teaching, give full play to the role of the main channel in the classroom education, and comprehensively promote the ideological and political construction of curriculum. This article first explores the ideological and political elements in each chapter of the course ‘Principles and Applications of Databases’ based on the characteristics of the course, teaching objectives, and teaching content; Then, starting from the background of the digital intelligence age, with the help of MOOC teaching platform, online and offline learning resources are integrated in the teaching process to construct the ideological and political education system of ‘Database Principles and Applications’; Finally, the teaching reform and practical experience in ideological and political construction were summarized to promote the balanced development of professional knowledge imparting and student value guidance.